Effective data visualization : the right chart for the right data - Evergreen, Stephanie D. H. (Los Angeles ; London ; New Delhi : SAGE Publications, 2017)
"Written by sought-after speaker, designer, and researcher Stephanie D.H. Evergreen, Effective Data Visualization shows readers how to create Excel charts and graphs that best communicate data findings. This comprehensive how-to guide functions as a set of blueprints--supported by research and the author's extensive experience with clients in industries all over the world--for conveying data in an impactful way. Delivered in Evergreen's humorous and approachable style, the book covers the spectrum of graph types available beyond the default options, how to determine which one most appropriately fits specific data stories, and easy steps for making the chosen graph in Excel. New to the Second Edition is a completely re-written chapter on qualitative data; inclusion of 9 new quantitative graph types; new shortcuts in Excel; and entirely new chapter on Sharing Your Data with the World which includes advice on using dashboards; and lots of new examples throughout. The Second Edition is also presented in full color"--
Our backbone : why we visualize -- When a single number is important : showing mean, frequency, and measures of variability -- How two or more numbers are alike or different : visualizing comparisons -- How we are better or worse than a benchmark : displaying relative performance -- What the survey says : showing likert, ranking, check-all-that-apply, and more -- When there are parts of a whole : visualizing beyond the pie chart -- How this thing changes when that thing does : communicating correlation and regression -- When the words have the meaning : visualizing qualitative data -- How things changed over time : depicting trends -- Sharing your data with the world -- It's about more than the buttons.
Includes bibliographical references and index.
Keywords: Visual communication; Charts, diagrams, etc; Presentation graphics software; Graphic design (Typography); Information visualization